Thanatology and terminal conditions in modern fiction and web literature: interdisciplinary discourse - T Bondarieva (Perioperative Medicine, 2023)
The article analyzes the thanatological motive and terminal conditions in fiction and web literature in an interdisciplinary context. Features of the image of death and various mediocre conditions in the web literature on the example of the internet novel “The Age of Glory and Hope” by Yevhenii Litvak are considered. The textual analysis revealed that web literature is more distributed, so the image of clinical death, predagonism, agony, etc. in the text of internet works may have a broader and more diverse semantic load than traditional fiction. It was found that death as a concept is represented by the following interpretations: euthanatic killing of some heroes by others, senseless suicide for dramatic plot twists, fair punishment and self-sacrifice for others and just death for fun. All these variations perform their artistic function in the text, while based on certain medical principles, which is expressed in the descriptions symptoms elements of the terminal conditions and death.